THE DEVELOPMENT OF MULTICULTURAL PARADIGMS AND UNDERSTAND FOR PEACEFUL COEXISTENCE - Nua-amnat, Rattiya; Brahmakappa, Akkaradecha; Thammamethee , PhramahaHai; Soonthondachar, Jaroonsak (Journal of MCU Social Science Review, 2022)
Objectives of this Action research were to develop and propose the guideline of the development of multicultural paradigms and understanding for peaceful coexistence. Methodology was the qualitative research, collected data interviewing 96 core group of leader and policy levels and documentary research. Action research by development of multicultural paradigms and understanding for peaceful coexistence for everybody of multicultural activity by A-I-C technique and evaluated by AAR technique Findings were as follows: 1. The development of multicultural paradigms and understanding for peaceful coexistence must be carried out in 5 dimensions: 1) prevention of mutual misunderstanding 2) creating equality, fairness and solidarity 3) recognition and respect for individual differences 4) Promotion of honesty, honesty and self-sacrifice for the common good 5) support of coexistence based on differences but not divisibility. And 2. The guideline of development of multicultural paradigms and understanding for peaceful coexistence was that everybody should encouraged according to the 10 commandments: 1) adherence to religious teachings 2) value and respect dignity and humanity 3) recognition and respect for differences between individuals 4) respect for human rights 5) equality and justice 6) maintaining the interests of the public 7) consciousness, volunteerism and public mind 8) duties responsible 9) critical verbal and opinion expression and 10) resolving conflicts in a peaceful manner.